The Legal Status of Diversion in Indonesia’s Juvenile Criminal Justice System - Riza Zulfikar (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2024)
This study examines the legal status of diversion within Indonesia's juvenile criminal justice system, which is explicitly regulated by Law No. 11 of 2012 and further reinforced by implementing regulations such as Supreme Court Regulation No. 4/2014 and National Police Regulation No. 8/2021. Although the provisions on diversion support a restorative justice approach and are normatively well-established, their implementation in practice continues to face numerous challenges. These include limited understanding among law enforcement officers, a shortage of qualified facilitators, and low participation from victims and the community in the diversion process. The objective of this research is to analyze the legal position of diversion in the juvenile justice system, identify the obstacles affecting its effectiveness, and recommend measures to enhance its successful implementation. This study employs a qualitative literature review method using normative, contextual, and comparative international approaches through an analysis of primary and secondary legal materials and relevant literature. The findings reveal that despite the adequacy of existing regulations, the realization of diversion in practice remains limited due to institutional weaknesses and the lack of effective dissemination and public awareness. These results highlight the need to strengthen the capacity of legal practitioners, develop diversion models that are contextually appropriate for Indonesia, and increase stakeholder participation. Overall, this study emphasizes the importance of structural reforms and the full commitment of all stakeholders to ensure that diversion functions optimally as a humane and just instrument within Indonesia's juvenile criminal justice system